2016
DOI: 10.1002/jat.3412
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetic model for ethyl tertiary‐butyl ether and tertiary‐butyl alcohol in rats: Contribution of binding to α2u–globulin in male rats and high‐exposure nonlinear kinetics to toxicity and cancer outcomes

Abstract: In cancer bioassays, inhalation, but not drinking water exposure to ethyl tertiary‐butyl ether (ETBE), caused liver tumors in male rats, while tertiary‐butyl alcohol (TBA), an ETBE metabolite, caused kidney tumors in male rats following exposure via drinking water. To understand the contribution of ETBE and TBA kinetics under varying exposure scenarios to these tumor responses, a physiologically based pharmacokinetic model was developed based on a previously published model for methyl tertiary‐butyl ether, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The expected values for V maxc and K m for ETBE were 1.11 mg/ hr/kg (29.6 μmol/hr/kg) and 0.09 mg/L (10.7 μM), respectively. The results had a large logarithmic standard deviation and were significantly lower than V maxc (499 μmol/ hr/kg) and K m (1248 μM) used in the rat PBK model of Borghoff et al (2017).…”
Section: Partition Coefficients and Metabolic Parameters Of Etbe In Humansmentioning
confidence: 69%
See 1 more Smart Citation
“…The expected values for V maxc and K m for ETBE were 1.11 mg/ hr/kg (29.6 μmol/hr/kg) and 0.09 mg/L (10.7 μM), respectively. The results had a large logarithmic standard deviation and were significantly lower than V maxc (499 μmol/ hr/kg) and K m (1248 μM) used in the rat PBK model of Borghoff et al (2017).…”
Section: Partition Coefficients and Metabolic Parameters Of Etbe In Humansmentioning
confidence: 69%
“…These metabolites are detected in rat and human urine (Amberg et al, 2000). Salazar et al (2015) and Borghoff et al (2017) independently developed rat ETBE PBK models, in which the mechanism of ETBE-induced tumorigenesis in the kidney and liver was elucidated by estimating the levels of its metabolite, TBA. The model of Salazar et al proposed two metabolism pathways from ETBE to TBA, whereas the model of Borghoff et al proposed a single oxidative metabolic pathway from ETBE to TBA.…”
Section: Introductionmentioning
confidence: 99%
“…And the result showed that cell viability decreased statistically after HT22 cells exposed to different concentrations of TBA compared to the control ( P < 0.05) (Figure ), which indicated that TBA had a direct cytotoxic effect on HT22 cells. As with MTBE, TBA also triggered oxidative stress in the kidney by forming adducts with DNA or α2u‐globulin . So, it is presumed that oxidative stress may contribute to the neurotoxicity mechanism of TBA.…”
Section: Discussionmentioning
confidence: 99%
“…TBA, an important intermediate of MTBE biodegradation, has also been shown to form adducts with DNA and α2u‐globulin in rats . It is known that protein adduct and DNA adduct are the biomarkers of oxidative stress or lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study published in 2019 by Hartmann and al., for example, the renal oncogenic effects of angiotensin II were investigated in Big Blue rats [79]. In a study published by Borghoff et al in 2017, the development of kidney tumors following exposure of rats to ethyl tertiary-butyl ether and tertiary-butyl alcohol was studied as well [80]. In a study by Balansky and al.…”
Section: Animal Models Of Kidney Carcinomas Induced By Other Factorsmentioning
confidence: 99%